2009
DOI: 10.1111/j.1651-2227.2009.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of documentation in potential abusive head injury of infants in a Paediatric Emergency Department

Abstract: In this study we found that among children with known risk factors for AHI, only a few had documentation regarding potential child abuse. The use of a standardized protocol could be helpful in the important work to help staff discover potential AHI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Documentation with free text will still be necessary because all information related to children's health and outcomes of provided care is not possible to be standardized. Further, documentation of sensitive psychosocial information such as family relationships and potential child abuse may need to be recorded with a common standardized language (34). Nurses do perceive documentation to be beneficial for providing high-quality care, and a prerequisite for improving documentation is to perform it in a structured and systematic manner (35).…”
Section: Discussionmentioning
confidence: 99%
“…Documentation with free text will still be necessary because all information related to children's health and outcomes of provided care is not possible to be standardized. Further, documentation of sensitive psychosocial information such as family relationships and potential child abuse may need to be recorded with a common standardized language (34). Nurses do perceive documentation to be beneficial for providing high-quality care, and a prerequisite for improving documentation is to perform it in a structured and systematic manner (35).…”
Section: Discussionmentioning
confidence: 99%
“…Svärd staff often do not document or assess indications of child abuse (Tingberg, Falk, Flodmark, & Ygge, 2009;Ziegler, Sammut, & Piper, 2005). In sum, studies aiming to analyze the processes of assessing at-risk children in somatic health care explored the information the assessments were based on and found that many different factors affected the outcome of the decision-making process with regard to reporting.…”
Section: Assessment Processes Of Children At Risk Within Pediatric Carementioning
confidence: 98%
“…However, several studies have reported a weak association between performed care and what is documented in the patient records, e.g. patient records do not accurately represent the reality of patients' problems, pressure-ulcer prevalence and prevention or signs and symptoms in potential abusive head injury in infants (Adamsen & Tewes 2000, Gunningberg et al 2008, Tingberg et al 2009).…”
Section: Introductionmentioning
confidence: 99%